The Effect of Adjunctive use of Dexmedetomidine and Metoral with Thiopental on Hemodynamic Status, Agitation, and Patient Satisfaction in Patients with Mood Disorders after Electroconvulsive Therapy - Mohammadi, Talat; Jamilian, Hamidreza; Alaghemand, Anita; Kamali, Alireza (Open Access Macedonian Journal of Medical Sciences, 2020)
AIM: The aim of our study was to determine the effect of adjunctive use of dexmedetomidine and metoral with thiopental on hemodynamic status, agitation, patient satisfaction, and duration of seizure in patients with mood disorders in electroconvulsive therapy (ECT). METHODS: This study is a randomized, double-blind, clinical trial. Sixty patients (18–60 years) according to DSM5 criteria had mood disorder and were candidates for ECT. Patients were randomly divided into two groups of 30 each. One group received 5.0 μg/kg dexmedetomidine 10 min before induction of thiopental, and the other group received 5.2 mg intravenous metoprolol immediately before ECT. Patients’ satisfaction, duration of seizure, and arterial oxygen saturation were evaluated. RESULTS: The mean age of both groups was approximately 37 years with the majority of men. No significant difference was found between the two groups in terms of age and sex, blood pressure (BP), heart rate (HR), duration of seizure, and arterial oxygen saturation before ECT. The mean BP and HR in the recovery were lower in the dexmedetomidine group than in the metoral group. Arterial oxygen saturation percentage was not significantly different between the two groups. The recovery time in the dexmedetomidine group was longer than the metoral group (p = 0.001). Post-ECT satisfaction was found to be higher in the dexmedetomidine group than in the metoral group and the mean agitation score was found to be higher in the metoral group. CONCLUSION: Both metoral and dexmedetomidine as adjuvants decrease the hyperdynamic responses of patients after ECT, whereas the effect of dexmedetomidine is more than metoral; on the other hand, neither dexmedetomidine nor metoral has any negative effect on seizure duration, but dexmedetomidine significantly prolonged recovery time as compared to metoral.